Legalitas dan Pendampingan Administrasi untuk Penguatan Sanggar Tari Rasat Eco Tarakan - Devi, Charitin; Ariani, Ariani; Margiyono, Margiyono; Kartini, Kartini; Pratiwi, Sulistya Rini; Putri, Ferica Christinawati; Rahmawati, Meylin; Agusriyanti, Rizky; Nainggolan, Yohanna Thresia (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Rasat Eco Dance Studio is one of the cultural community institutions that carries the mission of developing and preserving regional cultural values ​​and carrying out the process of cultural regeneration, especially the culture of the Dayak and Kalimantan tribes. This studio was established and operated on June 6, 2009. Since it began operating, Rasat Eco Dance Studio has carried out a series of cultural activities, one of which is Dance. This studio is located in Tarakan City, North Kalimantan Province. When this institution was first established, it did not have legality, and the administration was still not managed optimally. The management of Rasat Eco Dance Studio is not in accordance with the general procedures in establishing an institution, namely the fulfillment of the legality of the institution, so it is necessary to carry out mentoring and legalization activities regarding the management and administration of the institution to strengthen and increase capacity so that it can continue to work in carrying out cultural missions. The activities carried out include assistance in legalization and mentoring for the completeness of the administration of Rasat Eco Dance Studio and are held in Tarakan City, North Kalimantan Province. The output of this activity is legalization in the form of a deed of establishment of the institution and the completeness of the administration of the Rasat Eco Dance Studio institution.